Co2-immobilized intumescent material, cement composition, and concrete composition

CN122953216APending Publication Date: 2026-10-20DENKA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580020708.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-12
Publication Date
2026-10-20

AI Technical Summary

Benefits of technology

根据本发明,能够提供具有良好的膨胀性能和CO2固定化性能的CO2固定化膨胀材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

A CO2 immobilization expansion material comprising an ettringite-forming compound, wherein the ettringite-forming compound preferably comprises free lime as a mineral composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to CO2 immobilized expansion materials, cement compositions, and concrete compositions. Background Technology

[0002] From the perspective of the reliability, durability, and aesthetics of products and structures, reducing cracking in cement and concrete is important. Therefore, further technological advancements in expansive materials that improve these properties are desired.

[0003] In addition, in order to reduce the total amount of CO2 emitted during the manufacture of concrete products, it is effective to reduce cement usage by using a large amount of special admixtures and industrial by-products (blast furnace slag powder, fly ash, etc.) as cement substitutes, and various studies are currently underway.

[0004] This research also includes studies on technologies for enabling cementitious solids to absorb (immobilize) CO2. For example, Patent Document 1 discloses a method for forcibly absorbing CO2 or carbonizing it during manufacturing. Specifically, it discloses a method for immobilizing carbon dioxide, which includes a contact step in which the cementitious solid is brought into contact with a carbon dioxide-containing gas, thereby immobilizing the carbon dioxide contained in the carbon dioxide-containing gas into the cementitious solid.

[0005] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 2020-15659 Summary of the Invention

[0006] The problem that the invention aims to solve However, in the immobilization method of Patent Document 1, the water content in the carbon dioxide-containing gas is set to 1.5% or more, and the temperature is set to 75–175°C, but no material for immobilizing CO2 is disclosed or implied. Furthermore, no expansion material is disclosed.

[0007] Based on the above, the purpose of this invention is to provide a CO2 immobilized expansion material with good expansion properties and CO2 immobilization properties.

[0008] Methods for solving problems The inventors of this application conducted in-depth research to solve the aforementioned problems, and as a result, conceived the technical solution of the present invention as follows, finding that it can solve the problems. That is, the present invention is as follows.

[0009] [1] A CO2 immobilized expansion material comprising an ettringite-forming compound that generates ettringite.

[0010] [2] The CO2 immobilized expansion material as described in [1], wherein the aforementioned ettringite-forming compound contains free lime as a mineral component.

[0011] [3] The CO2 immobilized expansion material as described in [2] contains 10 to 70% by mass of the aforementioned free lime.

[0012] [4] The CO2 immobilized expansion material as described in any one of [1] to [3], wherein the aforementioned ettringite-forming compound comprises lapis lazuli as a mineral component.

[0013] [5] The CO2 immobilized expansion material as described in any one of [1] to [4], wherein the aforementioned ettringite-forming compound comprises sulfosilicate and / or calcium aluminum feldspar as a mineral composition.

[0014] [6] The CO2 immobilized expansion material as described in [5], wherein the content (total content) of the aforementioned sulfosilicon calcium stone and the aforementioned calcium aluminum feldspar in the aforementioned ettringite generating compound is 2 to 15 by mass.

[0015] [7] The CO2 immobilized expansion material as described in any one of [1] to [6], wherein the Blaine surface area of ​​the CO2 immobilized expansion material is 2000 to 6000 cm². 2 / g.

[0016] [8] The CO2 immobilized expansion material as described in any one of [1] to [7] is used for mixing with cement.

[0017] [9] A cement composition comprising cement and any one of [1] to [8] a CO2 immobilized expansion material.

[0018]

[10] A concrete composition comprising cement, aggregate and any one of [1] to [8] CO2 immobilized expansion material.

[0019] Invention Effects According to the present invention, a CO2 immobilized expansion material with good expansion properties and CO2 immobilization properties can be provided. Detailed Implementation

[0020] Hereinafter, one embodiment of the present invention (this embodiment) will be described in detail.

[0021] [CO2 Immobilized Expanding Material] The CO2 immobilized expanding material of this embodiment includes an ettringite-forming compound that produces ettringite. In this embodiment, in a cement composition or concrete composition containing the CO2 immobilized expanding material, the ettringite formed during its curing process absorbs carbon dioxide (CO2) into its crystals, thereby absorbing CO2. Furthermore, due to the expanding properties of the CO2 immobilized expanding material, a good expanding effect can be achieved.

[0022] Here, "curing" refers to the following state: the compressive strength reaches 2.5 N / mm² according to the method specified in JIS R 5201:2015 "Physical Test Methods for Cement". 2 above.

[0023] Regarding the CO2 absorption mentioned above, although it also depends on conditions such as humidity, it is expected that the generated ettringite will absorb a large amount of CO2 (3 moles, 4.2 moles, or 4.6 moles relative to 1 mole of ettringite) through any of the following formulas (1) to (3).

[0024] Formula (1): 3CaO·Al2O3·3CaSO4·32H2O+3CO2→3CaCO3+Al2O3(gel)+3CaSO4·2H2O+26H2O Formula (2): 3CaO·Al2O3·3CaSO4·31.1H2O+4.6CO2→3CaCO3+Al2O3·10.4H2O·1.6CO2+3CaSO4·0.5H2O+19.2H2O Formula (3): 3CaO·Al2O3·3CaSO4·30.9H2O+4.2CO2→3CaCO3+Al2O3·7.9H2O·1.2CO2+3CaSO4·2H2O+17.0H2O As for the ettringite-forming compound involved in this embodiment, there is no particular limitation as long as it is a compound that forms ettringite. For example, at least one of the following can be selected from the group consisting of calcium sulfoaluminate, calcium aluminate, calcium fluoroaluminate, calcium chloroaluminate, alinite, Na2O·8CaO·3Al2O3, alum, sulfates, etc.

[0025] From the viewpoint of good strength presentation and CO2 immobilization amount, a combination of at least one of calcium sulfoaluminate and calcium aluminate with sulfate is preferred.

[0026] Here, the calcium aluminate (CA) involved in this embodiment is a general term for compounds with CaO and Al2O3 as the main components. For example, amorphous compounds with CaO and Al2O3 as the main components, and crystalline calcium aluminate represented as CaO·2Al2O3, CaO·Al2O3, 12CaO·7Al2O3, 11CaO·7Al2O3·CaF2, and 3CaO·3Al2O3·CaF2, etc.

[0027] The preferred CaO / Al2O3 molar ratio of CA is in the range of 0.45 to 3, and more preferably in the range of 0.8 to 2. By setting the CaO / Al2O3 molar ratio to 0.45 or higher, sufficient initial strength can be achieved. Furthermore, by setting the CaO / Al2O3 molar ratio to 3 or lower, sufficient flowability and service life can be obtained.

[0028] As mentioned above, calcium aluminate can be used in any form, whether crystalline or amorphous. Amorphous materials obtained by rapidly cooling melts in an electric furnace or similar environment are preferred. If the amorphous content is 60% or more by mass, it exhibits superior short-term strength. The proportion of amorphous material (amorphous degree) is determined by powder X-ray diffraction / Rietveld analysis.

[0029] The calcium sulfoaluminate (CSA) involved in this embodiment is manufactured by calcining and pulverizing raw materials such as lime, sulfate raw materials such as gypsum, and alumina raw materials such as bauxite in a converter at around 1300°C to 1600°C.

[0030] Regarding CSA, for example, there is a substance obtained by mixing raw materials in a molar ratio of CaO:Al2O3:CaSO4 of 3:3:1, calcining and pulverizing it, but there is no particular limitation. This is called kosherite (3CaO·3Al2O3·CaSO4).

[0031] From the viewpoint of expansion rate, it is preferable that the ettringite-forming compound contains free lime as its mineral composition. The ettringite-forming compound preferably contains 3 to 80% by mass of free lime, more preferably 15 to 65% by mass of free lime. By containing 3 to 80% by mass of free lime, excellent expansion properties can be ensured.

[0032] Furthermore, regarding the ettringite-forming compound, from the viewpoint of ensuring expansion rate and strength, it is preferable to include lapis lazuli as a mineral component. The ettringite-forming compound preferably contains 1 to 30% by mass, more preferably 3 to 25% by mass of lapis lazuli. By including 1 to 30% by mass of lapis lazuli, excellent expansion properties and strength can be achieved simultaneously.

[0033] Regarding the ettringite-forming compound, from the viewpoint of efficient CO2 fixation, it is preferable that the mineral composition includes sulfosilicate and / or calcium aluminate. In the ettringite-forming compound, the total mass percentage of sulfosilicate and calcium aluminate is preferably 2-15% by mass, more preferably 3-10% by mass. By including 2-15% by mass of sulfosilicate and calcium aluminate, CO2 fixation can be more efficient. To achieve the above-mentioned sulfosilicate content, for example, it can be adjusted by mixing silica as a reagent into the raw material.

[0034] Examples of sulfates mentioned above include alkali metal sulfates and alkaline earth metal sulfates.

[0035] Alkali metals that can be used as alkali metal sulfates include lithium, sodium, and potassium, with sodium being the preferred choice. Alkali metal sulfates can be used alone or in combination with two or more.

[0036] Alkaline earth metals that can be used as sulfates include magnesium and calcium, with calcium being preferred. Alkaline earth metal sulfates can be used alone or in combination with two or more. There are no particular restrictions on the particle size or shape of alkaline earth metal sulfates; for example, those with a Blaine surface area of ​​4000–8500 cm² can be cited. 2 A substance of approximately / g.

[0037] Here, calcium sulfate is preferred as an alkaline earth metal sulfate, and anhydrous gypsum (anhydrous calcium sulfate), hemihydrate gypsum (calcium sulfate hemihydrate), and dihydrate gypsum (calcium sulfate dihydrate) are examples. Among these, anhydrous gypsum is preferred.

[0038] Relative to 100 parts by weight of calcium sulfoaluminate, the sulfate, calculated in anhydrous form, is preferably 7 to 60 parts by weight, more preferably 15 to 58 parts by weight, and even more preferably 20 to 57 parts by weight.

[0039] Furthermore, relative to 100 parts by weight of calcium aluminate, the preferred amount, calculated in anhydrous form, is 40 to 160 parts by weight, more preferably 42 to 157 parts by weight, and even more preferably 45 to 155 parts by weight. As long as the content of alkaline earth metal sulfates is within the above range, long-term strength performance tends to be excellent.

[0040] From the viewpoint of good strength and CO2 immobilization, it is preferable that the ettringite compound is calcium sulfoaluminate and / or calcium aluminate, and that it includes lapis lazuli as a mineral component. Lapis lazuli preferably contains 10% by mass or more, more preferably 15% by mass or more, in the ettringite compound. The amount of lapis lazuli can be adjusted by changing the composition ratio of CaO, Al2O3, and SO3 in the raw materials. It should be noted that there is no specific upper limit, but in practice it is 80% by mass.

[0041] Furthermore, from the viewpoint of good strength presentation and CO2 immobilization amount, the calcium sulfate in the ettringite formation compound, which is a mineral component, is preferably 2 to 75% by mass, more preferably 10 to 70% by mass.

[0042] The mineral composition of free lime, lapis lazuli, sulfosilicate, calcium aluminate, and calcium sulfate in the compounds formed by ettringite can be determined by XRD / Rietveld method.

[0043] From the viewpoint of maximizing its functionality, the Blaine specific surface area of ​​the ettringite-formed compound is preferably 1,500 to 8,000 cm². 2 / g, more preferably 2,000 to 7,000 cm³ 2 / g.

[0044] From the viewpoint of maximizing its functionality, the Blaine surface area of ​​the CO2 immobilization expansion material in this embodiment is preferably 1,500 to 8,000 cm². 2 / g, more preferably 2,000 to 7,000 cm³ 2 / g, more preferably 2,000 to 6,000 cm⁻¹ 2 / g.

[0045] From the viewpoint of maximizing its functionality, the ettringite-forming compound is preferably 80% by mass or more, and more preferably 90% by mass or more, in the CO2 immobilization expansion material.

[0046] Furthermore, when 50 parts by mass of water are mixed with 100 parts by mass of CO2 immobilized expansion material, and the mixture is cured for 24 hours, the CO2 immobilization rate of the resulting solidified body after standing at 20°C and 60% RH in an environment with a CO2 concentration of 5% for 24 hours is preferably 9% or more, and more preferably 10% or more.

[0047] Here, the immobilization rate can be calculated by the ratio of the number of CaO moles after the reaction to the number of CaO moles before the reaction (CaO-mol after the reaction / CaO-mol before the reaction).

[0048] The CO2 immobilized expansion material described above can be used directly for various purposes or mixed with other materials. Considering the long-term durability of the cured body and the application of existing technologies related to maintenance and management, it is preferred to use it in cement or concrete.

[0049] [Cement compositions and concrete compositions] The cement composition involved in this embodiment includes the CO2 immobilized expansive material and cement described above. Furthermore, the concrete composition involved in this embodiment includes the CO2 immobilized expansive material and cement described above.

[0050] It should be noted that the cement composition in this embodiment refers to the general term for cement, cement paste and mortar.

[0051] From the viewpoint of achieving good expansion and CO2 immobilization, the content of the CO2 immobilization expansion material is preferably in the range of 5 to 90 parts by mass relative to 100 parts by mass of cement, and more preferably in the range of 30 to 80 parts by mass.

[0052] The cement used in this embodiment is not particularly limited, and can include various types of cement such as ordinary, early-strength, ultra-early-strength, low-heat, and medium-heat cements; various mixed cements containing blast furnace slag, fly ash, silica fume, etc.; environmentally friendly cement (ecological cement) made from municipal solid waste incineration ash and sewage sludge incineration ash; siliceous materials such as metakaolin and calcined clay; and commercially available microparticle cements. Various types of cement and mixed cements can also be used after being pulverized into microparticles. Additionally, cement with adjusted amounts of commonly used cement components (such as gypsum) can also be used. In this embodiment, from the viewpoints of heat of hydration, drying shrinkage, and filling properties, ordinary Portland cement and early-strength Portland cement are preferred.

[0053] Furthermore, considering manufacturing costs and strength performance, the Blaine specific surface area of ​​cement is preferably 2,500–7,000 cm². 2 / g, more preferably 2,750 to 6,000 cm³ 2 / g.

[0054] The Blaine surface area in this specification can be determined according to JIS R 5201 (physical test method for cement).

[0055] Examples of fine aggregates used in this embodiment include river sand, mountain sand, land sand, sea sand, silica sand, crushed sand, lime crushed sand, blast furnace slag fine aggregate, and recycled fine aggregate. The type and content of fine aggregates can be selected according to the target mechanical strength of the solidified concrete.

[0056] Examples of coarse aggregates used in this embodiment include crushed stone obtained by crushing andesite, rhyolite, hard sandstone, limestone, etc., river gravel, mountain gravel, land gravel, blast furnace slag coarse aggregate, and recycled coarse aggregate. The rock type, size, and content of the coarse aggregate can be selected according to the target mechanical strength of the solidified concrete.

[0057] This embodiment may also contain various additives. Examples include water-reducing agents, AE agents, foaming agents, shrinkage-reducing agents, waterproofing agents, rust inhibitors, tackifiers, polymers, water-retaining agents, pigments, water-repellent agents, and anti-whitening agents.

[0058] Example The present invention will be specifically illustrated by the following examples, but the present invention is not limited thereto.

[0059] [Experimental Example 1] <Preparation of CO2 Immobilized Expanded Materials> Calcium carbonate reagent, aluminum hydroxide reagent, calcium sulfate reagent, and silicon dioxide reagent were mixed in accordance with the composition shown in Table 1 below, and heat-treated at 1350°C for 3 hours to adjust the Blaine surface area to 3500 cm². 2 / g, to prepare ettringite-derived compounds, which are then used as CO2 immobilization expansion materials.

[0060] (evaluate) <Intensity> A composition with a water / powder mass ratio of 0.5 and a fine aggregate / powder mass ratio of 3.0 was molded into test specimens of 40×40×160mm, and the strength was determined at 1, 3, and 7 days of age (JIS R 5201:2015 "Physical Test Methods for Cement"). A compound was formed by mixing 5% by mass of ettringite relative to the powder.

[0061] It should be noted that the "powder" mentioned above refers to the total amount of ettringite-derived compounds and cement (ordinary Portland cement). Additionally, silica sand was used as the fine aggregate. After demolding one day after the material was matured, carbonation curing was carried out under the conditions of temperature: 20℃, humidity: 60%RH, and CO2 concentration: 5%.

[0062] <CO2 solid absorption (CO2 content, CO2 immobilization rate)> A neat paste with a water / powder mass ratio of 0.5 was molded into test specimens measuring 20×20×80mm. After demolding at 1 day, the specimens were subjected to carbonation curing under conditions of 20℃, 60%RH, and 5% CO2 concentration. A compound was formed by mixing 6.7% by mass of ettringite relative to the powder.

[0063] Then, after the test specimens were crushed to a size of less than 90 μm at the specified age, the CO2 content was determined by coulometric method.

[0064] It should be noted that the "powder" mentioned above refers to the total of ettringite compounds and cement (ordinary Portland cement).

[0065] <Expansion> A composition with a water / powder mass ratio of 0.5 and a fine aggregate / powder mass ratio of 3.0 was molded into test specimens of 40×40×160mm, and the length change rate was measured at 7 and 28 days of age (JIS A 6202:2017 "Expansive materials for concrete"). After demolding at 1 day of age, carbonation curing was carried out under the conditions of temperature: 20℃, humidity: 60%RH, and CO2 concentration: 5%.

[0066] It should be noted that the term "powder" refers to the total amount of ettringite compound and cement (ordinary Portland cement). The powder contains 6.7% by mass of ettringite compound. Additionally, silica sand was used as the fine aggregate.

[0067] [Table 1]

Claims

1. A CO2 immobilized expansion material comprising an ettringite-forming compound that generates ettringite.

2. The CO2 immobilization expansion material as described in claim 1, wherein, The ettringite-forming compound contains free lime as a mineral component.

3. The CO2 immobilization expansion material as described in claim 2, comprising 10-70% by mass of the free lime.

4. The CO2 immobilized expansion material as described in claim 1, wherein, The ettringite-forming compound contains lapis lazuli as a mineral component.

5. The CO2 immobilization expansion material as described in claim 1, wherein, The ettringite-forming compounds comprise, as a mineral composition, sulfosilicate and / or calcium aluminum feldspar.

6. The CO2 immobilized expansion material as described in claim 5, wherein, The content of the sulfosilicon calcium ore and the calcium aluminum feldspar in the ettringite compound is 2-15% by mass.

7. The CO2 immobilization expansion material as described in claim 1, wherein, The Blaine surface area of ​​the CO2 immobilized expansion material is 2000–6000 cm². 2 / g.

8. The CO2 immobilized expanding material as described in claim 1, used for mixing with cement.

9. A cement composition comprising cement and a CO2 immobilized expansion material as described in any one of claims 1 to 8.

10. A concrete composition comprising cement, aggregate and CO2 immobilized expansion material as described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Stabilization method of carbon dioxide

    JP2020015659A